The Activation and Consumption of Factor IX - Nossel, H. L (Thrombosis and Haemostasis, 1964)
The results of these experiments support previous observations that factor IX activity is increased approximately ten fold by incubation with calcium and optimal amounts of product XI a. The finding of a reciprocal relationship between maximal product IX a formation and residual factor IX provides further evidence in favour of the hypothesis that factor IX behaves as a substrate when activated by product XIa. This reciprocal relationship between percentage active product formed and residual percentage of the inactive factor is similar to that shown to occur when factor XI is activated by factor XII and celite (Nossel 1964).